Westward dharma : Buddhism beyond Asia - Prebish, Charles S.; Baumann, Martin, 1960- (University of California Press, 2002)
The first authoritative volume on the totality of Buddhism in the West, Westward Dharma establishes a comparative and theoretical perspective for considering the amazing variety of Buddhist traditions, schools, centers, and teachers that have developed outside of Asia.
Keywords: Buddhism -- Missions -- History.; Buddhism -- History -- 20th century.; Globalization -- Religious aspects -- Buddhism.; Bouddhisme -- Missions -- Histoire.; Bouddhisme -- Histoire -- 20e siècle.; Mondialisation -- Aspect religieux -- Bouddhisme.; RELIGION -- Buddhism -- History.; RELIGION -- Buddhism -- General.; Globalization -- Religious aspects -- Buddhism; Buddhism; Buddhism -- Missions; Boeddhisme.; Westerse wereld.; Bouddhisme.; Mission (Religion); Histoire.; 20e siècle.; Occident.; 1900 - 1999; asia.; australia.; buddhism scholars.; buddhism.; buddhist practices.; buddhist studies.; buddhist teachings.; buddhist traditions.; comparative religions.; dharma.; diaspora.; egalitarianism.; ethics.; europe.; global religion.; history of buddhism.; israel.; north america.; psychology.; religious philosophy.; religious scholars.; south africa.; theoretical approach.; theoretical perspective.; western buddhists.; western philosophy.; western thought.; western world.; zen.; History